FORMULAIC EXPRESSIONS IN CONVERSATION - Teshaboyeva Nafisa Zubaydulla qizi Scientific advisor: Jizzakh branch of the National university of Uzbekistan named after Mirzo Ulug’bek. The faculty of psychology, the department of Foreign languages; Philology; teaching languages: English Akramova M (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Formulaic expressions are an integral part of natural conversation, providing speakers with pre-established, predictable phrases that facilitate smooth and efficient communication. These expressions, which include greetings, idioms, polite requests, and conversational fillers, serve various functions such as reducing cognitive load, conveying social meaning, and enhancing fluency. For language learners, mastering formulaic expressions is essential to achieving conversational competence, as these expressions help bridge gaps in understanding and allow for more natural interactions. This article explores the role of formulaic expressions in conversation, highlighting their importance in both language production and comprehension, as well as their cultural and social implications. By examining their types, functions, and significance in communication, this study underscores the value of formulaic expressions in achieving fluency and effective communication in everyday interactions.